Potensi Pembiayaan Usaha Mikro, Kecil dan Menengah oleh Perbankan di Wilayah Perbatasan Kalimantan Barat Tahun 2008 - Afrizal (Jurnal Aplikasi Manajemen, 2009)
The aim of this study was to describe and analyze the characteristics and potency of micro-small middle enterprises (UMKM) and to understand its costing potential by formal finance institution (banking) in border area of West Kalimantan. This border-site research determined two regencies, Kabupaten Sanggau (Entikong) and Kabupaten Sambas (Sajingan Besar). Some data used was primary one (sixty samples) that was obtained through field research and some questionaries and in-depth interview as well as secondary data. The findings indicated that the dominant economic activities performed in the border of Entikong and Sajingan Besar was trading and services, in which inhabitants and foreign workers as marketing coverage, as well as Serawak people as main target market. The infrastructure condition in this area was relatively bad and didn't have representative market yet. Another finding was the lack share and unavailability of fund and money sources with accessible return and the lack existence of formal financial supplier (capital investors) for small-middle enterprises. The dominant capital investors in this border area was Credit Union, without any banking existed.